Temporal trends of ventilatorassociated pneumonia in adult intensive care units in the municipality of Goiânia, Goiás, Brazil - Faria Alves, Ana Caroliny; de Lima Vieira dos Santos , Silvana; Gomes Resende de Souza da Silva , Alexsandra; Coelho do Nascimento , Júlio César; Galdino Júnior , Hélio; Martins Mendonça , Katiane; Bisinoto Alves , Sergiane; Carneiro Cunha Neves, Heliny (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
Given the potential for morbidity and mortality of ventilator-associated pneumonia (VAP), the profile of these infections in adult intensive care units was evaluated in the city of Goiânia. Data were collected from a secondary base in the Department of Prevention and Control of Infection in Health Services, of the Municipal Health Department of Goiânia, from 2014 to 2016, in private (82.7%), public (17.2%), and philanthropic (6.0%) health care services. The rate of use of mechanical ventilation did not change significantly over the three years (32.6%). However, there was a decrease in the mean of VAP incidence density, and in 2016 there was a reduction of 7% in the 90th percentile. These reductions highlight the benefit of the implementation and adherence to bundles by the multidisciplinary team. KEY WORDS: Pneumonia; ventilator-associated; ventilators; mechanical; disease notification.